Experience-dependent neuroplasticity of the developing hypothalamus: integrative epigenomic approaches - Vogel Ciernia, Annie (Epigenetics, 2018)
Augmented maternal care during the first postnatal week promotes life-long stress resilience and improved memory compared with the outcome of routine rearing conditions. Recent evidence suggests that this programming commences with altered synaptic connectivity of stress sensitive hypothalamic neurons. However, the epigenomic basis of the long-lived consequences is not well understood. Here, we employed whole-genome bisulfite sequencing (WGBS), RNA-sequencing (RNA-seq), and a multiplex microRNA (miRNA) assay to examine the effects of augmented maternal care on DNA cytosine methylation, gene expression, and miRNA expression. A total of 9,439 differentially methylated regions (DMRs) associated with augmented maternal care were identified in male offspring hypothalamus, as well as a modest but significant decrease in global DNA methylation. Differentially methylated and expressed genes were enriched for functions in neurotransmission, neurodevelopment, protein synthesis, and oxidative phosphorylation, as well as known stress response genes. Twenty prioritized genes were identified as highly relevant to the stress resiliency phenotype. This combined unbiased approach enabled the discovery of novel genes and gene pathways that advance our understanding of the epigenomic mechanisms underlying the effects of maternal care on the developing brain.